Elucidating the behavioral response of stored product insects to fungal volatiles in the wind tunnel and simulated warehouses - Silvernail, Lauren; Quellhorst, Hannah; Bruce, Alex; Morrison III, W.R. (My University, 2018)
Post-harvest pest insects can cause significant amounts of damage to stored products in and around food facilities, reducing quantity and quality of grains. Post-harvest insects have been attributed to billions of dollars in agricultural loss via yield loss and the cost of mitigation measures. Early detection of insect pests is crucial to preventing infestations and losses since some species of stored product pests are becoming resistant to common control options. Numerous detection methods are available, but many are time consuming and ineffective, leading to a need for more effective and practical monitoring methods. Grain oils have been used to induce behavioral responses in the red flour beetle (Triboliumcastaneum) and the lesser grain borer (Rhyzoperthadominica), but fungal volatiles may be an even stronger attractant to these species.
Keywords: Fall 2018